Effects of aeration on flavor compounds in immobilized primary fermentation - Virkajärvi, Ilkka; Lindborg, Katri; Kronlöf, Jukka; Pajunen, Esko (BrewingScience, 1999)
Continuous immobilized primary fermentation has been studied since the last century, but has not yet fulfilled expectations. There are two main biological difficulties for continuous primary fermentation: achieving and maintaining the desired flavor and preventing contaminations. One traditional way of controlling the flavor of beer is by aeration of wort prior to pitching. We explored the effects of aeration in immobilized primary fermentation. The fermentation system used consisted of two packed bed reactors and a buffer tank between the reactors. An industrial wort and an industrial brewer’s yeast strain were used. The wort was aerated by mixing air into the wort stream just before the inlet of the first reactor (pre-column). The air was diluted with carbon dioxide and both were filtered twice through a PTFE 0,2 μm membrane (domnick hunter Ltd., Durham, UK). The feed rates of synthetic air and carbon dioxide were changed independently according to a Box-Hunter experimental design while keeping the feed rate of the wort constant. The results were analyzed using a computer program for experimental design Modde 3.0, (Umetri AB, Uppsala, Sweden) and mathematical models for the concentrations of higher alcohols and two acetate esters in the out-flow from the pre-column were created. It was found that both low air feed and high air feed with low carbon dioxide feed stimulated the 3-methyl butyl acetate production in the pre-column. The main column seemed to even out the changes in the aroma compounds analyzed, so that their final levels were relatively insensitive to air supply in the range studied.